Awareness, perceived barriers and factors affecting willingness for Organ Donation among the first- and second-degree relatives of deceased in a tertiary care hospital of Northern India - Swain, Rajanikanta; Prasad, Hari; Lalwani, Sanjeev; Pooniya , Shashank (Journal of Indian Academy of Forensic Medicine, 2021)
Increased demand and poor availability of organs are the causes of illicit trade of organs. Inadequate availability of organs is due to poor awareness for organs donation. In recent past, law (Transplantation of Human Organ and tissue act) has been amended to curb the illicit organ trafficking, facilitate organs donation and create awareness. To know the awareness, perceived threat and factors affecting the willingness to donate organs after the amendment of recent act a study was conducted in a tertiary care hospital from October 2014 to September 2015. All participants are the 1st and 2nd degree relatives of the deceased persons came to the tertiary care hospital for autopsy. Data was collected in a semi-structured pretested questionnaire. Around 69% of participants have heard about organ donation. Perceived barriers included complication after donation (42%), tedious process (31.6%), religious beliefs (22%) and no improvement of receiver after transplantation (12%). Knowledge and attitude are main dependent factors associated with willingness to donate organs. Hence Organ donation is critical for patients requiring organ transplantation. It can be improved by increasing awareness.